Modern Architecture in the Design of Syiah Kuala University Student Sports Center - livia aditiya (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Syiah Kuala University currently has a Sport Center, but due to the overall lack of maintenance and the lack of facilities that support activities so that only a few activities can be accommodated, making this building ineffective and cannot function optimally as it should.Therefore, in this writing, the aim is to create or design a Sport Center of Syiah Kuala University design that is able to facilitate activities in Unsyiah. This design will take the theme of Modern Architecture.The use of the theme of modern architecture itself is motivated by the function of the Sport Center to be planned as the Sport activity. Modern architectural themes are expected to be able to provide characteristics that are suitable for both space and users.Modern architecture is a term given to buildings that have characteristic styles that prioritize simplicity of form and remove all ornaments. Based on the book "The Le Corbusier Guide Third edition" which explains the concept of the Five Points of Le Corbusier which is five points that become a new approach to Modern Architecture design that gives freedom in the development of designs with new forms.Keywords: Sport Center, Modern Architecture, Le Corbusier, Five Points of Le Corbusier